The articles Perbandingan Penerapan Program Green School Dalam Mengembangkan Pendidikan Karakter Anak Usia 4-6 Tahun - Nanik Ilmiyah Ilmiyah (Universitas Muhammadiyah Gresik, 2022)
Many found the nature of children who are not good, especially to the environment. Such as littering, lack of a sense of responsibility, lack of sense of independence, and lack of discipline so that the impact on children's character in the future. This study aims to determine the implementation of the Green school program in Kindergarten ABA 16 Takerharjo and to find out how big the difference in character education for children aged 4-6 years. This study uses quantitative research, with a sample of 40 per institution, the samples in this study were students at TKM 65 Futuhatul Ulum Roomo and TK ABA 16 Takerharjo. The instrument used in the form of a questionnaire or questionnaire then tested for validity, reliability test, normality test 0.220, homogeneity test 0.887 and Kolmologror Smirnov test in testing the hypothesis. The results showed that there was no difference in character education between the two institutions, namely TKM 65 Futuhatu Ulum Roomo and TK Aisyiyah Bustanul Athfal 16 Takerharjo. It was proven by the Kolmologrov Smirnov test that it was significant at 0.220 > 0.05. Keywords: Green School Program, Character Education, Children Age 4-6 Years.